2015
DOI: 10.1017/jie.2015.11
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Place, Learning Together: Perspectives and Reflections on an Educational Partnership Formation With a Remote Indigenous Community School

Abstract: Sustainable partnership formation in a remote Indigenous community involves social, cultural and political considerations. This article reports on the project, ‘Sharing Place, Learning Together: Supporting Sustainable Educational Partnerships to Advance Social Equity’, funded by the Melbourne Social Equity Institute (MSEI) at the University of Melbourne (UoM). The project's aims were to document insights into working with communities and educators in a remote community school in Western Arnhem Land, and to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The literature comprised three distinct institutional categories: six publications primarily examined university led aspiration and/or outreach programs targeting secondary school students (Godinho, Wooley, Webb, & Winkel, 2015;Peralta, Cinelli, & Bennie, 2018;Shinkfield, 2014;Smith et al, 2015;Thomas, Bronwyn, Kirkham, & Parry, 2014;Thorn & Flodin, 2015); two publications focused on vocational education and training (VET) programs based at secondary schools (Oliver, Grote, Roschecouste, & Exell, 2013;Pham, Page, Sivamalai, & Woolley, 2012); and four related to experiential place-based learning programs with a local employment focus (Altman & Fogarty, 2010;Fogarty, 2012;Fogarty & Schwab, 2012;Kral, 2010). Ten publications reported studies conducted with students enrolled in community-based schools (Altman & Fogarty, 2010;Burton & Osborne, 2014;Fogarty, 2012;Fogarty & Schwab, 2012;Godinho et al, 2015;Kral, 2010;Peralta et al, 2018;Osborne et al, 2017;Smith et al, 2015;Thomas et al, 2014), and four publications reported studies conducted with remote Indigenous students who attended boarding schools (Oliver et al, 2013;Pham et al, 2012;Shinkfield, 2014;Thorn & Flodin, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The literature comprised three distinct institutional categories: six publications primarily examined university led aspiration and/or outreach programs targeting secondary school students (Godinho, Wooley, Webb, & Winkel, 2015;Peralta, Cinelli, & Bennie, 2018;Shinkfield, 2014;Smith et al, 2015;Thomas, Bronwyn, Kirkham, & Parry, 2014;Thorn & Flodin, 2015); two publications focused on vocational education and training (VET) programs based at secondary schools (Oliver, Grote, Roschecouste, & Exell, 2013;Pham, Page, Sivamalai, & Woolley, 2012); and four related to experiential place-based learning programs with a local employment focus (Altman & Fogarty, 2010;Fogarty, 2012;Fogarty & Schwab, 2012;Kral, 2010). Ten publications reported studies conducted with students enrolled in community-based schools (Altman & Fogarty, 2010;Burton & Osborne, 2014;Fogarty, 2012;Fogarty & Schwab, 2012;Godinho et al, 2015;Kral, 2010;Peralta et al, 2018;Osborne et al, 2017;Smith et al, 2015;Thomas et al, 2014), and four publications reported studies conducted with remote Indigenous students who attended boarding schools (Oliver et al, 2013;Pham et al, 2012;Shinkfield, 2014;Thorn & Flodin, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, it is recommended that developing education that is specific and accessible to the Practitioners enables communities to grow their health workforce (National Aboriginal and Torres Strait Islander Health Council, 2003; Rose, 2014). As well, training local people enhances social capital by building their capacity to respond to identified needs (Toombs, 2011; Giri et al ., 2012; Sherwood and Kendall, 2013; Best and Stuart, 2014; Godinho et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sharing the construction of CE with regional Practitioners can enhance culturally derived knowledge and skills leading to increased social capital and better health outcomes (Sherwood and Kendall, 2013; Godinho et al ., 2015). However, this approach requires health and education providers to acknowledge the vital role that practitioners have in maintaining and improving the health status of Aboriginal and Torres Strait Islander communities.…”
Section: Discussionmentioning
confidence: 99%